PHYSIOTHERAPY MANAGEMENT IN THE HANDLING OF JUMPERS KNEE SINISTRA WITH ULTRASOUND AND EXERCISE THERAPY AT RSUD HARDJONO PONOROGO - Fadhilah Ilmi, Dhiki; Saputra Perdana, Suryo; Kingkinnarti (JTH: Journal of Technology and Health, 2025)
Patellar tendinitis or jumper's knee is an injury due to overuse of the patellar tendon that often occurs in athletes, especially in jumping and running activities. This case study aims to evaluate the effectiveness of a combination of ultrasound therapy and exercise therapy program (eccentric, isometric, stretching, and strengthening exercises) in the management of jumper's knee sinistra in a 16-year-old female student who is active in volleyball at RSUD Hardjono Ponorogo. This research method is a case study, conducted three times a meeting in two weeks. Evaluation includes pain measurement using the Numeric Rating Scale (NRS), joint motion scope (LGS) with a goniometer, and functional ability using the Jette Scale. The results showed a decrease in motion pain from 4/10 to 1/10, tenderness from 3/10 to 0/10, and an increase in left knee LGS from 80° to 95°. In addition, there was an improvement in functional ability, especially in squatting and walking activities, although activities up and down stairs still require further training. The combination of exercise therapy and ultrasound proved effective in reducing pain, increasing joint flexibility, and improving functional ability in a case of jumper's knee sinistra.